Implicaciones de la globalización y del Tratado de Libre Comercio en el sector agroalimentario y en la soberanía alimentaria colombiana (2006)
ABSTRACT: The main purpose of this document is to analyze The United States and Colombia opening agreement that has been thought to enhance economic growth and prosperity between both countries and what globalization represents for Colombia on its environment, on culture, on political systems, on economic development and prosperity. Furthermore, to discuss the opportunities generated by the trade and the controversies that has been expressed by people on different media. This document concludes with all the issues that could affect Colombia governability on agriculture and economy.